Cooperativas de material reciclável no interior do Estado do Ceará e o fenômeno da precarização do trabalho - Martins, David Paiva (2013)
Nowadays labor has become flexible and precarious, direct consequence of an antagonistic movement related to Fordism. The flexibility of labor carries in itself the breakage of labor rights and the advancement of toil in the laborer’s private circles. This way, the precariousness of labor derives directly from that labor flexibility movement. The arising of cooperatives in 19th century opens new possibilities to thinking capital and labor per se, however the ideals of mutual cooperation and self-management propitiate the appearance of false collectives, disseminating various models of labor outside the sign of cooperative. The gathering of recyclable materials, perpetrated basically in cooperatives, assemble those workers without perspective of getting back to the formal laboring market, at the same time it offers a precarious labor with few or null possibilities of change. This way the present study, which was part of the research to obtain the title of Master by the Post-Graduation Program in Psychology of the Federal University of Ceará – UFC, was devoted to analyze the precariousness of labor and the working relationships that are present in a cooperative of recyclable materials, located in Icó, Ceará. For that matter, 05 individuals directly related to the gathering activity were interviewed based in a qualitative approach. Then, based on those interviews and according to Alonso’s social hermeneutics, categories were cast and analyzed, all of them common and present in every speech. It was considered that the precarious labor performed by the gatherers is based not only in physical activity, but in the subjectivity of them too, making even more difficult to reflect deeply about their precarious condition and inhibiting the restoration of labor rights and of the private time demanded by the precarious labor.